2020
DOI: 10.1038/s41598-020-72754-5
|View full text |Cite
|
Sign up to set email alerts
|

Spotlight on the invasion of a carabid beetle on an oceanic island over a 105-year period

Abstract: The flightless beetle Merizodus soledadinus, native to the Falkland Islands and southern South America, was introduced to the sub-Antarctic Kerguelen Islands in the early Twentieth Century. Using available literature data, in addition to collecting more than 2000 new survey (presence/absence) records of M. soledadinus over the 1991–2018 period, we confirmed the best estimate of the introduction date of M. soledadinus to the archipelago, and tracked subsequent changes in its abundance and geographical distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 88 publications
0
27
0
Order By: Relevance
“…In particular, the impacts of invasive alien species on biodiversity may profoundly alter the functioning of communities and ecosystems (Braun et al 2019;Papier et al 2019), in turn altering the delivery of ecosystem services (Castro-Diez et al 2016), biodiversity and human health (Elbakidze et al 2018;Shackleton et al 2019;Kumar Rai and Singh 2020;Pyšek et al 2020). When expanding their range, several invasive alien species can also act as ecosystem engineers, gradually transforming invaded communities and existing ecological structures (Guy-Haim et al 2017;Lebouvier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the impacts of invasive alien species on biodiversity may profoundly alter the functioning of communities and ecosystems (Braun et al 2019;Papier et al 2019), in turn altering the delivery of ecosystem services (Castro-Diez et al 2016), biodiversity and human health (Elbakidze et al 2018;Shackleton et al 2019;Kumar Rai and Singh 2020;Pyšek et al 2020). When expanding their range, several invasive alien species can also act as ecosystem engineers, gradually transforming invaded communities and existing ecological structures (Guy-Haim et al 2017;Lebouvier et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that this economic burden might have risen steadily along with the signi cant increase in establishment of alien terrestrial invertebrate species reported in the literature over past decades (Roques et al 2009;Roques 2010;Seebens et al 2017). Several invasive invertebrates, in particular insects, also greatly affect biodiversity, with critical consequences for native species (Lebouvier et al 2020;Liu et al 2020). Predictions of future range shifts that accompany globalization and climate change will likely add to these effects (Bebber et al 2013;Bellard et al 2013;Bertelsmeier et al 2015).…”
Section: Introductionmentioning
confidence: 75%
“…It is increasingly clear on some sub-Antarctic islands that non-native invasive predators (carabid beetles) have strongly negative impacts on many, often endemic, members of the native terrestrial invertebrate communities, which do not include analogous functional guilds (e.g. Lebouvier et al 2020 ). Such species can be considered ecosystem engineers.…”
Section: Introductionmentioning
confidence: 99%
“…If this happens, it can have serious impacts on Antarctic species and ecosystems (e.g. Hughes et al 2013 ; Molina-Montenegro et al 2019 ; Lebouvier et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%